2014
DOI: 10.2135/cropsci2013.06.0414
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Fiber Quality Traits with an Emphasis on Elongation in Upland Cotton

Abstract: The upland cotton (Gossypium hirsutum L.) industry in the United States has shifted from a domestic market to an export‐based market that mandates simultaneous improvements of yield and various fiber traits to maintain competitiveness. Fiber elongation (ability to stretch before breaking) is one of the key fiber parameters in determining yarn quality. It is a trait that is largely understudied due to an absence of monetary incentives for growers to produce high‐elongation cotton fibers. Five upland genotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…Within populations, this correlation did not hold for F 2:5 strains derived from ESU624 ´ ELSU33 and TAM22 ´ SID84. Ng et al (2014) reported similar observations regarding the negative correlation between UHML and Elon in experimental populations grown at College Station. Fiber micronaire responded negatively to selection for UHML across all populations.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Within populations, this correlation did not hold for F 2:5 strains derived from ESU624 ´ ELSU33 and TAM22 ´ SID84. Ng et al (2014) reported similar observations regarding the negative correlation between UHML and Elon in experimental populations grown at College Station. Fiber micronaire responded negatively to selection for UHML across all populations.…”
Section: Discussionsupporting
confidence: 66%
“…Considering that realized heritability provides an estimate of how much of the selection differential imposed was observed as a response in the progeny, these results suggest that early generation selection for UHML and Str is highly effective at College Station, with the exception of progeny derived from ESU624 ´ ELSU33. The results further suggest that the negative correlation between UHML and Elon is more than an artifact attributable to the positive correlation between UHML and Str, and combined with the results reported by Ng et al (2014), suggest that further investigation into the negative relationship between UHML and Elon is warranted. Several F 2:5 strains with improved UHML and/or Str and no associated reduction in LP were identified within each population, providing further evidence that the negative relationship between fiber quality and lint yield is, at least in part, attributable to repulsion phase linkage.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…From that preliminary study and results from previous diallel analysis, four parents, DEV, MD9, TAM, and ARK, were chosen for the GMA study (Ng et al, 2013). From that preliminary study and results from previous diallel analysis, four parents, DEV, MD9, TAM, and ARK, were chosen for the GMA study (Ng et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the four parents, that is, ARK, MD9, and DEV, were previously studied in a diallel analysis for fiber elongation by Ng et al (2013), and the results from that study suggested further dissection into gene actions governing fiber elongation. The small sample sizes of these parental plants prohibited the use of HVI to measure elongation, and the Stelometer was chosen as an alternative, as previous study has shown good correlations between the two systems (Ng et al, 2013). Six distinctive families were created, with each family consisting of six generations: P 1 , P 2 , F 1 , F 2 , BCP 1 , and BCP 2 .…”
Section: Methodsmentioning
confidence: 99%